Design, Construction and Testing of a Dry Sand Sieving Machine - Oladeji Akanni Ogunwole (Journal of Applied Sciences and Environmental Management)
This paper reports on the design, construction and Testing of a dry sand sieving machine. The sample to be sieved is uniformly graded. The coefficient of uniformity is 1.11, thus the machine design does not sieve larger particles such as gravel. The slip calculated is 36% which enabled the proper configuration of the V-belt. The theoretical efficiency of the machine calculated is 97%.